Pentingnya literasi keuangan di pedesaan Kampung Cipeundeuy, Desa Cikarang Kabupaten Garut Selatan - Iskandar, Fatimah Nurjannati (Nur Science Institute, 2025)
Financial literacy is a fundamental asset for rural communities in addressing various financial challenges. Financial literacy also plays an important role in economic growth and societal circulation. Financial literacy has become a significant focus in many countries in recent years, as a good understanding of finance plays an important role in helping individuals and groups avoid mistakes in financial decision-making. One of the targets of literacy activities is in South Garut, especially in Cipeundeuy Village, Cikarang. In Cipendeuy Village, economic businesses are owned by individuals and groups ranging from agriculture, such as rice, sugar, coffee, fruits, and plants. Community service activities through financial literacy aim to find potential knowledge related to basic finance that is still inadequate. This activity provides new knowledge for the community in understanding the ability to plan finance properly and correctly, understand the concept of investment and long-term savings, understand rights and obligations and believe that the selected financial products and services can improve community welfare, and avoid financial activities that are not by applicable regulations. Based on the results of the socialization regarding financial literacy, from 50 participants who previously understood financial literacy, 35 people became 50 participants.